Phosphorylation by Inorganic Phosphate of the Plasma Membrane H(+)-ATPase from Red Beet (Beta vulgaris L.) - de la Vara, Luis E. González (1990)
The phosphorylation of plasma membrane proteins from red beet (Beta vulgaris L.) by radioactive inorganic phosphate was studied. Only few proteins were phosphorylated, among them was one polypeptide with an apparent molecular weight of about 100,000. The phosphorylation of this protein was decreased when orthovanadate was present in the reaction mixture, or when the phosphorylated protein was treated with hydroxylamine. These facts suggest that this protein is a transport ATPase which is phosphorylated in a carboxyl group during the catalytic cycle. This protein was identified immunologically as the plasma membrane H(+)-ATPase. The phosphorylation level of this enzyme was enhanced by dimethyl sulfoxide, whereas potassium ions did not have a significant effect on this level unless ATP was present. ATP stimulated the phosphorylation by inorganic phosphate. This stimulation was more apparent in the presence of potassium ions.